TRAINING AND MENTORING OF SCIENTIFIC WRITING BASED ON CORPUS LINGUISTICS - Febri Taufiqurrahman; Martutik Martutik; Didin Widyartono; Anang Santoso; Novi Eka Susilowati; Cicik Tri Jayanti; Suparno Suparno; Abdul Syukur Ibrahim (Universitas PGRI Palembang, 2020)
Al-Hikam Student Islamic Boarding School is founded by KH. A. Hasyim Muzadi in Malang City. This Islamic boarding school has been built with the aim of realizing the integrity of science and religion as a whole. With this educational model, it is hoped that there will be no scientific dichotomy so that religious beliefs have a scientific-rational basis and science is always protected by religious values. In the current era of the industrial revolution 4.0, the students who graduated from Islamic boarding schools are expected to be able to produce scientific works with their ability of religious knowledge. However, in reality, the abilities and interests of the students are very low. By writing scientific works based on the language corpus, the students can express their ideas and ideas in writing more easily. Therefore, this service is carried out to prepare students to be able to write scientific papers properly and correctly. Training is not enough, there should be an assistance so that the students get direct experience on how to write scientific papers. Selected articles are recommended for submission to national or international journals